A clinical study to compare the efficacy of 2 electric toothbrushes in plaque removal - Dörfer, Christof; Pretzl, Bernadette; Bethlenfalvy, Eric von; Staehle, Hans Jörg; Pioch, Thomas (Journal of clinical periodontology, 2001)
To compare the cleaning efficacy of a powered toothbrush with 3-dimensional brush head action (Braun Oral-B 3D Plaque Remover D15) and a high-speed “microtation” brush with an additional “microbrush®-clip” (Rowenta Dentasonic MH921S).